What If Endoscopic Eradication Therapy for Esophageal Neoplasia Is Not Good Enough?. Issue 2 (June 2022) - Watson, Thomas J.
Endoscopic eradication therapies have become the standard of care for most cases of Barrett's esophagus with high-grade dysplasia or intramucosal adenocarcinoma, largely replacing esophagectomy. While associated with high rates of complete elimination of dysplastic mucosa and superficially invasive esophageal cancer, as well as an excellent complication profile, endoscopic eradication requires strict adherence to established diagnostic and treatment protocols as well as disciplined follow-up. Even with appropriate attention to detail, esophageal neoplasia can persist or recur following endoscopic resection or ablation. The managing physician must remain cognizant of the limitations of endoscopic approaches and consider surgical alternatives to treatment when they fail or are exceeded. Esophagectomy, performed at experienced centers on appropriately selected patients with early-stage neoplasia, can be undertaken with the expectation of cure, low perioperative mortality, acceptable morbidity, and good long-term quality of life. Prompt surgical referral should occur when endoscopic eradication has been ineffective so as not to deprive the patient with early esophageal neoplasia the chance of cure.